Differences in Glycemic Abnormalities Between Primary Aldosteronism and Essential Hypertension: A Systematic Review and Meta-Analysis - Manosroi, Worapaka; Atthakomol, Pichitchai; Wattanawitawas, Pittaporn; Buranapin, Supawan (Frontiers in Endocrinology, 2022)
Background: The relationship of glycemic abnormalities between primary aldosteronism (PA) patients and essential hypertension (EH) patients is still debatable. This meta-analysis aimed to explore differences in the prevalence of glycemic abnormalities and levels of abnormal glucose metabolism in PA and EH patients. Methods: A search was performed using PubMed, Scopus, Cochrane and Web of Science databases from their inception through January 2022. Inclusion criteria for this study were 1) observational studies which contained specific data of interest, 2) studies including data which compared adult PA and EH patients and 3) studies which used appropriate methods to diagnose PA. Risk ratio (RR) or standardized mean difference (SMD) with a 95% confidence interval (95% CI) was calculated. Results: Twenty-six studies involving 53,186 patients were included in the meta-analysis. Patients with PA demonstrated significantly higher overall incidence of glycemic abnormalities than patients with EH (RR 1.54; 95% CI (1.20,1.98)). Risk of diabetes mellitus (DM) and impaired glucose tolerance (IGT) in PA patients were higher than in EH patients (RR 1.27; 95%CI (1.08, 1.49) and RR 2.99; 95%CI (1.74, 5.16), respectively). There was no statistically significant difference of risk between these groups for impaired fasting glucose (IFG) (RR 1.70; 95%CI (0.55, 5.26). Moderate heterogeneity was observed in overall glycemic abnormalities outcomes. A high level of heterogeneity was observed for IFG, while the level was low for DM and IGT. Conclusions: PA patients have a higher risk of glycemic abnormalities than in EH patients. Further study should be conducted to investigate underlying mechanisms of glycemic abnormalities in PA.